Metode One Day Five Ayat Dalam Meningkatkan Kemampuan Menghafal Santri Di Pondok Pesantren Al-Aqobah 4 Jombang - Tri Fahad Lukman Hakim; Rahmat; Abd Haris (Program Studi Pendidikan Agama Islam, 2022)
The method of memorizing the Qur’an is one of model that can be used to be developed in finding the right pattern for memorizing and help the memorizer in overcoming difficulties during the process of memorizing Qur’an. The one day five verse method used by Al-aqobah 4 Jombang islamic boarding school is a method modified by the foundation’s caregivers to make it easer for students to memorize the Qur’an. The focus of the researh in this paper is the implementation of one day five verse method and its implications for the ability to memorize students at the Al-aqobah 4 islamic boarding school Jombang. The aims of this study are : 1) to determine and analyze the implementation of the one day five verse method at the Al-aqobah 4 islamic boarding school Jombang. 2) to find out and analyze the implications of the one day five verse method in improving the memorizing ability of student at Al-aqobah 4 islamic boarding school Jombang. This research use a case study approach, and qualitative reseach. Methods of data collection using interview, observations, and documentation. Data analysis used the mathew miles and michael hubermen model, namely data reduction in presenting data and drawing conclusions (verification).The result of the one day five verse methode improving the memorizing ability of student at Al-aqobah 4 Jombang islamic boarding school, implementation of the one day five verse method at Al-aqobah 4 islamic boarding school Jombang, based on the result of the study indicate that the implementation has gone very well. This is evidenced, a) Before students memorize, student correct their reading first. b) Al-aqobah 4 islamic boarding school Jombang applies a clear memorization target because it is structured. c) the one day five verse method repeats the verse. d) evalution of memorization conducted by Al-aqobah 4 islamic boarding school Jombang by looking at the ability of student. The impilication of the one day five verse method in improving students memorization skills that memorization is more structured, so the target of memorization skills that memorization is more structured, so the target of memorization of memorization can be achieved. a) the one day five verse method makes it easier for student to memorization because of the systematic memorization because of the systematic memorization program. b) supporting factors for memorizing the memorization target of each student are not the same, giving rewards to student who are able to achieved the target, holding events, bringing in motivating figures in memorizing. c) the constaint is the problem of disciplinary aplication in the field.